2018
DOI: 10.22146/majkedgiind.24852
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ethanol extract of soursop leaf (Annona muricata L.) on Adhesion of Streptococcus mutans ATCC 35668 to hydroxyapatite discs

Abstract: The demineralization of dental hard tissues can be caused by dental plaque. Dental plaque contains various components, especially bacteria attached to the extracellular matrix. Streptococcus mutans (S. mutans) has extracellular glucan as adhesin that is important in the attachment mechanism of tooth surface. The natural substance can be used for preventing plaque formation by inhibiting the attachment of S. mutans. Soursop plant has been used in treating various diseases. The leaves of the soursop (Annona muri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 0 publications
2
11
1
Order By: Relevance
“…triangularis adhesion to the plastic surface and contact lens. This result is in agreement with the previous study reported on A. muricata inhibited the adhesion of Streptococcus mutans on hydroxyapatite discs, resulting in plaque forming inhibition (Rahman et al,2018). It was also observed that flat and adjacent trophozoites adhered to the surface via several acanthopodia in the control, while the treated trophozoites demonstrated shrunken cells.…”
Section: Discussionsupporting
confidence: 93%
“…triangularis adhesion to the plastic surface and contact lens. This result is in agreement with the previous study reported on A. muricata inhibited the adhesion of Streptococcus mutans on hydroxyapatite discs, resulting in plaque forming inhibition (Rahman et al,2018). It was also observed that flat and adjacent trophozoites adhered to the surface via several acanthopodia in the control, while the treated trophozoites demonstrated shrunken cells.…”
Section: Discussionsupporting
confidence: 93%
“…Alkaloids are also able to disrupt the integrity of peptidoglycan components in bacterial cells. Peptidoglycan is a component of cell wall in bacteria that any disruption in peptidoglycan will inhibit wall layer formation and could lead to cell death (Rahman et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Besides that, alkaloids can also interfere with the integrity of the peptidoglycan component in bacterial cells. Peptidoglycan is a component of the building of bacterial cell walls so that interference will cause the cell wall layer not to form intact and cause cell death [17].…”
Section: Antibacterialmentioning
confidence: 99%
“…The antibacterial mechanism possessed by tannins is its ability to inhibit the synthesis of chitin used to form cell walls in fungi and damage the cell membrane so that fungal growth is inhibited. Tannins are also lipophilic compounds that are easily attached to the cell wall and cause damage to the cell wall [17].…”
Section: Antibacterialmentioning
confidence: 99%